KINERJA PEGAWAI ADMINISTRASI KEPENDUDUKAN DI KANTOR CAMAT RUMBAI KOTA PEKANBARU - Perliana, Winda; Sahuri, Chalid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Population Administration Employee Performance In Pekanbaru City District Office Tassel. Measurements in a performance that is very necessary with a view to identify and improve the effectiveness of performance on a system. In this study, the analysis focused on the device's performance in the District Rumbai in providing services. Duties of employees who provide services to the community. But basically the task has not been effectively carried on by employees of the District, for a variety of community service current affairs in the region to protests the District Tassel always is less effective and efesiennya these services, it is marked by the performance of employees in service delivery to the public is worse than carried on by the private sector. In addition, in accordance with the growing extracting information that the administrative services in the District Rumbai population is problematic and confusing and does not have the right time and the accuracy obviously. Furthermore, many people who complain of the results of population in the district administrative services Tassel, as at the time obtain birth certificate, KK, ID cards from UPTD in the District Tassel, to get the letter to be confronted by the public services that are less effective and efficient, because slow process of publishing the letter so that people feel dissatisfied with the services obtained. The concept of the theory used to use performance measurement indicators: quantity of work, quality of work, time utilization, Cooperation. By measuring the performance of the employee and the District can provide insight into the quality of service performance in the conduct population administration and determine the factors that affect and hinder the performance of the District of service delivery. Departing from the authors were interested in examining these issues and seeks to provide solutions to improve services to the community in District Rumbai Pekanbaru City. The purpose of this study to determine the performance of the device the District in providing services to the community, in addition to determine the factors that hinder the performance of the District in providing services to the community Tassel. The results of this study indicate that the performance of the device has not been effective and the District Tassel inhibiting factors include employees not yet fully understand the duties and obligations as well as the principles of the ideal of service.